Retrograde signaling via axonal transport through signaling endosomes - Naoya Yamashita (Elsevier, 2019)
Neurons extend axons far from cell bodies, and retrograde communications from distal axons to cell bodies and/or dendrites play critical roles in the development and maintenance of neuronal circuits. In neurotrophin signaling, the retrograde axonal transport of endosomes containing active ligand-receptor complexes from distal axons to somatodendrite compartments mediates retrograde signaling. However, the generality and specificity of these endosome-based transportations called "signaling endosomes" remain to be elucidated. Here, I summarize the discovery of semaphorin3A signaling endosomes, the first example other than neurotrophins to regulate dendritic development via AMPA receptor GluA2 localization in dendrites. The molecular components of Sema3A and neurotrophin signaling endosomes are distinct, but partially overlap to regulate specific and common cellular events. Because receptors are transported back to the cell bodies, neurons must replenish receptors on the growth cone surface to ensure continued response to the target-derived ligands. Recent findings have demonstrated that retrograde signaling endosomes also induce anterograde delivery of nascent receptors in neurotrophin signaling. The coupling between anterograde and retrograde axonal transport via signaling endosomes therefore plays a critical role in regulating proper neuronal network formation. Keywords: Sema3A, NGF, Axonal transport, Signaling endosomes, Receptor internalization